Pengaruh Disiplin Kerja Dan Punishment Terhadap Kinerja Karyawan Pada PT. Balikpapan Forest Industries (BFI) Desa Jenebora Kabupaten PPU (Studi Kasus Pada Divisi Engineering) - Damitha Rande (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the effect of work discipline and punishment on employee performance. The research method used is a quantitative method to determine the effect between two variables. The sample used was 65 respondents who were employees of PT. Balikpapan Forest Industries (BFI) using nonprobability sampling with saturated sampling method. Data collection techniques using observation, interviews, questionnaires, documentation. The analytical tool used is multiple linear regression with the help of SPSS version 25. The results of this study indicate that the work discipline and punishment variables simultaneously together have a significant effect on employee performance, the work discipline variable partially has a significant effect on employee performance, the punishment variable partially has a significant effect on employee performance.